Challenges In Implementing Islamic Financial Institution Pension Funds In Indonesia - Laili Fathul Hidayah; Ummi Kaltsum Karunianing Utami; Fatih Fuadi; Muhammad Iqbal (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
Islamic Financial Institution Pension Funds (DPLK Syariah) represent a long-term financial instrument aimed at ensuring retirees’ economic security while adhering to Islamic principles. Despite the rapid growth of the Islamic finance industry in Indonesia, the development of Islamic pension funds remains relatively limited compared to conventional pension schemes. This article seeks to systematically examine the key challenges faced in the implementation of DPLK Syariah in Indonesia and to formulate strategic efforts to strengthen its development. Employing a qualitative approach, this study adopts a literature review method by analyzing scholarly articles, regulatory frameworks, policy reports, and relevant academic publications published between 2022 and 2025. The findings reveal that the implementation of DPLK Syariah is constrained by multidimensional challenges, including regulatory disharmony, limited availability of sharia-compliant investment instruments, low public literacy and participation, as well as institutional and human resource capacity weaknesses. Furthermore, the dominance of conventional pension funds continues to restrict market penetration for Islamic pension schemes. To address these challenges, this study proposes several strategic measures, such as enhancing Islamic financial literacy, promoting product and technological innovation, expanding sharia-based investment instruments, strengthening governance and human capital, and improving regulatory harmonization. This study is expected to contribute both conceptually and practically to policymakers, industry practitioners, and academics in fostering a more inclusive, competitive, and sustainable Islamic pension fund ecosystem in Indonesia.